Pedagogical cognitive knowledge in an effort to improve students' cognitive abilities: Systematic literature review - Fitri Rahmadhani; Aldeva Ilhami; Yuni Ernika Saputri (Universitas Ahmad Dahlan, 2022)
This researcher aims to improve pedagogical cognitive knowledge in an effort to improve students' cognitive abilities. This research method is the SLR (Systematic Literature Review) method. So that the selected literature is relevant search using the keywords